The vaccine industry after the COVID-19 pandemic: An international perspective - Félix Lobo (South Centre, 2024)
The purpose of this report is to analyze the impact that the COVID-19 pandemic has had on the vaccine industry from an international perspective. The objective is to learn from the experience and contribute to the design of better tools for future vaccine development and manufacturing, as we must be prepared for future emerging infectious diseases with the potential for global expansion. This industry makes fundamental contributions to global social welfare, but from a business point of view it is complex and difficult to manage, and from an economic point of view it is an industry that does not fit the paradigm of competitive market efficiency with notorious market failures. We examine the impact of the pandemic on innovation and the scientific, technological and industrial development of vaccines and find that certain elements of the industry's structure have changed, while others have remained. We also summarize the lessons learned from the deployment of some public policies to boost supply and drive demand, paying particular attention to the inequity in the global distribution of vaccines and to the COVAX program. We conclude that some of the policies have been very effective, while others have not fully achieved their objectives. From the achievements and limitations, lessons can be drawn for the reformulation and expansion of global public policies that would stimulate R&D, manufacturing, distribution and access.
Keywords: 300; Access to Medicines; Access to Vaccines; COVID-19; COVID-19 Technology Access Pool (C-TAP); COVID-19 Vaccines Global Access (COVAX); Global Health; Health; Innovation; Intellectual Property; Pandemic; Pandemics; Public Health; Research and Development (R&D); Technology Transfer; TRIPS; TRIPS Agreement; TRIPS Waiver; Vaccine Equity; Vaccine Industry; Vaccine Inequity; Vaccine Nationalism; Vaccines